Population Genomic Structure and Genome-Wide Linkage Disequilibrium in Farmed Atlantic Salmon (Salmo salar L.) Using Dense SNP Genotypes - Barria, Agustin; López, Maria E.; Yoshida, Grazyella; Carvalheiro, Roberto; Lhorente, Jean P.; Yáñez, José M. (Frontiers in Genetics, 2018)
Chilean Farmed Atlantic salmon (Salmo salar) populations were established with individuals of both European and North American origins. These populations are expected to be highly genetically differentiated due to evolutionary history and poor gene flow between ancestral populations from different continents. The extent and decay of linkage disequilibrium (LD) among single nucleotide polymorphism (SNP) impacts the implementation of genome-wide association studies and genomic selection and provides relevant information about demographic processes of fish populations. We assessed the population structure and characterized the extent and decay of LD in three Chilean commercial populations of Atlantic salmon with North American (NAM), Scottish (SCO) and Norwegian (NOR) origin. A total of 123 animals were genotyped using a 159K SNP Axiom® myDesignTM Genotyping Array. A total of 32 K SNP markers, representing the common SNPs along the three populations after quality control were used. The principal component analysis explained 78.9% of the genetic diversity between populations, clearly discriminating between populations of North American and European origin, and also between European populations. Admixture analysis separated these populations in two clusters, one of this clusters was composed by NAM, while the other was comprised by SCO and NOR populations joined. NAM had the lowest effective size, followed by SCO and NOR. Large differences in the LD decay were observed between populations of North American and European origin. An r2 threshold of 0.2 was estimated for marker pairs separated by 7,800 Kb, 64 Kb and 50 Kb in the NAM, SCO and NOR populations, respectively. In this study we show that this SNP panel can be used to detect association between markers and traits of interests and also to capture high-resolution information for genome-enabled predictions. Also, we suggest the feasibility to achieve similar prediction accuracies using a smaller SNP data set for the NAM population, compared with samples with European origin which would need a higher density SNP array.